In praise of litigation - Lahav, Alexandra D. (Oxford University Press, 2017)
It is not difficult to find critics of America's famously litigious society. We have more lawyers per capita than anywhere else. Critics say we are unmatched in our willingness to sue, pointing to anecdotes of frivolous suits such as a man who sued his drycleaner over a pair of pants or parents who sued a school when their son broke his leg going down a slide head first. The critics contend that the primary beneficiaries of litigation are attorneys themselves, and that the main effect of excessive litigiousness is reduced business innovation. The tort reform movement that they champion-dedicated to limiting the reach of lawsuits and in some cases eliminating certain types of suits altogether-has become a powerful force in America politics and law. The tort reform movement has had some real successes in limiting what can reach the courts, but there have been victims too. As Alexandra Lahav shows, it has become increasingly difficult for ordinary people to enforce their rights. In the grand scale of lawsuits, actually crazy or bogus lawsuits constitute a tiny minority ; in fact, most anecdotes turn out to be misrepresentations of what actually happened. In In Praise of Litigation, Lahav argues that critics are blinded to the many benefits of lawsuits. The majority of lawsuits promote equality before the law, transparency, and accountability. Our ability to go to court is a sign of our strength as a society and enables us to both participate in and reinforce the rule of law. In addition, joining lawsuits gives citizens direct access to governmental officials-judges-who can hear their arguments about issues central to our democracy, including the proper extent of police power and the ability of all people to vote. It is at least arguable that lawsuits have helped spur major social changes in arenas like race relations and marriage rights, as well as made products safer and forced wrongdoers to answer for their conduct. In this defense, Lahav does not ignore the obvious drawbacks to litigiousness. It is expensive, stressful, and time consuming. Certainly, sensible reforms could make the system better. However, many of the proposals that have been adopted and are currently on the table seek only to solve problems that do not exist or to make it harder for citizens to defend their rights and to enforce the law. This is not the answer. In Praise of Litigation offers a level-headed and law-based assessment of the state of litigation in America as well as a number of practical steps that can be taken to ensure citizens have the right to defend themselves against wrongs while not odiously infringing on the rights of others. "--